Death spiral of European offset? - Matthews, Ron; Anicetti, Jonata (Taylor and Francis, 2021)
This paper is concerned with evaluating the impact of the Procurement Directive, 2009/81/EC, on defence offset in Europe. The aim of the Directive was to reduce the extent of Article 346 derogations based on offset. Indirect offset has disappeared, and while the evidence is patchy, direct offset appears to be declining. This gradual demise of offset is in line with the global trend, especially among advanced countries. Offset is increasingly becoming a developing country phenomenon.